2008
DOI: 10.1111/j.1741-5446.2008.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

What Should We Teach as Controversial? A Defense of the Epistemic Criterion

Abstract: There is an emerging consensus that to teach something as controversial is to present it as a matter on which different views are or could be held and to expound those different views as impartially as possible. This raises an important normative question that has yet to receive the attention it deserves from educational theorists: how are we to decide which topics to teach in this way? The answer suggested by Robert Dearden is that we should apply the epistemic criterion: a matter should be taught as controve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
125
1
24

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(151 citation statements)
references
References 4 publications
(1 reference statement)
1
125
1
24
Order By: Relevance
“…The teacher does this because of the belief that he or she does not have any convincing arguments for one particular position. In Hand's (2008) words, the topic is controversial.…”
Section: The Peaceable School: Concretising the Relationship Between mentioning
confidence: 97%
See 2 more Smart Citations
“…The teacher does this because of the belief that he or she does not have any convincing arguments for one particular position. In Hand's (2008) words, the topic is controversial.…”
Section: The Peaceable School: Concretising the Relationship Between mentioning
confidence: 97%
“…If an approach to moral education seems to have consequences for the theological convictions of students and their organised worldviews, we can examine whether this influence is an intentional aim of the programme or approach, or a non-intentional side effect and whether attention is paid to religious and non-religious organised worldview convictions in a directive or nondirective manner (Hand, 2008). …”
Section: The Peaceable School: Concretising the Relationship Between mentioning
confidence: 99%
See 1 more Smart Citation
“…Hess (2009b) suggested that same-sex marriage should be discussed as it relates to either Constitutional issues (e.g., whether forbidding same-sex marriage violates the 14th Amendment) or policy issues (e.g., whether Congress should overturn the Defense of Marriage Act [DOMA]). While these framings of the issue have ethical dimensions (Harris, 1996), they are examined primarily as a political issue (a need to decide what to do) rather than as a moral issue (Hand, 2007(Hand, , 2008. Such a framing holds the potential to make what the New York Times recently called "one of the most contentious and politically charged social issues of the day .…”
Section: Same-sex Marriage As a Cpimentioning
confidence: 97%
“…6 Even if it were the case that exposure to religious views that differed from one's own did lead to increases in levels of civic harmony, it is worth noting, first, that this is unlikely to justify a privileged (in curriculum terms) and expansive subject which examines differing religions in considerable depth, such a the stand-alone, compulsory subject that is taken by pupils aged 5-16 in England and Wales. Rather, it might merit consideration in some part of a curriculum, such as, for example, Citizenship Studies, in the UK, where questions of toleration and the social benefits of mutual respect amongst citizens can be studied more directly and directively (see Hand 2008;White 2004).…”
Section: Toleration and Mutual Respectmentioning
confidence: 99%